The Implications Of The Supreme Court Decision Number 1664k/PDT/2017 On The Settlement Of Credit Disputes In PT. BPR Universitas Gadjah Mada - Natalia Margareta Br Perangin-Angin; Hasdiana Juwita Bintang; Dina Andiza (International Journal of Society and Law, 2025)
Credit dispute resolution is an important aspect in financial risk management in banking institutions, including PT. BPR (People's Credit Bank). As a financial institution serving the micro market segment , PT. BPRs are often involved in credit disputes that require legal settlement. The Supreme Court's decision Number 1664K/PDT/2017 has proven to be an important milestone in the Indonesian legal system and a precedent in handling credit disputes. This study aims to find out how the general arrangement regarding the right of dependents, to find out the factors that cause debtors not to pay credit, and to find out the implications of the Supreme Court's decision in decision number 1664K/Pdt/2017. This study uses a qualitative method with an analytical descriptive approach, where this type of research is normative legal research. Based on the findings of the research, the Supreme Court determined that the cassation application filed by Identika was rejected and charged Identika with case costs. This decision confirms that the execution and auction carried out by PT. BPR UGM through KPKNL has been legally valid, and that the aspects that Identika objected to are irrelevant in the context of resistance to this execution.